The Effect of Service Tax Officials, Penalties for Late Payments and Reporting on The Taxpayer Compliance Non-star Hotels - Ely Kartikaningdyah; R. Qinanti Nuzurawan (Journal of Applied Accounting and Taxation, 2019)
This research conducted to determine the effect of service tax officials, penalties for late-payments and reporting on the taxpayer compliance non-star hotels. This research was conducted at Dinas Pendapatan Kota Batam. Mechanical determination of sample using a purposive sampling technique with a total sample of 116 taxpayers. The type of data used is primary data. Methods of data collection are done by questionnaire. Data using multiple regression analysis with SPSS V.20.0. These results indicate that the service tax officials, penalties for late-payments and reporting have a positive and significant effect on the taxpayer compliance non-star hotels. The limitations in the study are the lack of understanding of respondents to the statements in the questionnaire and caring attitude and seriousness in answering statements. The study also suggested that Dinas Pendapatan Kota Batam provides socialization with both the taxpayer so they better understand the tax penalties and cause sanctions fines on taxpayers.